Modelling the hydrology of the Greenland ice sheet - Karatay, Mehmet Rahmi (The University of Edinburgh, 2011)
This thesis aims to better understand the relationships between basal water pressure, friction, and sliding mechanisms at ice sheet scales. In particular, it develops a new subglacial hydrology model (Hydro) to explicitly predict water pressures in response to basal water production and water injection from the surface. Recent research suggests that the Greenland ice sheet (gis) is losing a substantial volume of ice through dynamic thinning. This process must be modelled to accurately assess the contribution of the gis to sea-level rise in future warming scenarios. A key control on dynamic thinning is the presence of water at the ice-bed interface; Zwally et al. (2002) highlight the importance of supraglacial lakes' impact on basal ice dynamics, a process now con rmed by Das et al. (2008) and Shepherd et al. (2009). Many studies focus on the effects of surface meltwater reaching the bed of the gis but the underlying processes are often ignored. Geothermal, strain, and frictional melting, which evolves with basal hydrology, provide the background basal pressure profile that surface meltwater perturbates. Without understanding how these heat terms affect the background profile it is difficult to define basal boundary conditions in models and therefore difficult to model the dynamic response of the gis to surface melting. Hydro tracks subglacial water pressures and the evolution of efficient drainage networks. Coupled with the existing 3D thermomechanical ice sheet model Glimmer, model outputs include effective pressure N and the efficient hydraulic area. Defining frictional heat flux and basal traction as functions of N allow the modelling of seasonal dynamic response to randomly draining supraglacial lakes. Key results are that frictional heat flux, as a function of N, caps potential runaway feedback mechanisms and that water converges in topographic troughs under Greenland's outlet glaciers. This leads to a background profile with low N under outlet glaciers. Therefore, outlet glaciers show a muted dynamic ...